2012
DOI: 10.1038/ejcn.2011.222
|View full text |Cite
|
Sign up to set email alerts
|

Lipid, lipoprotein and apolipoprotein profiles in European adolescents and its associations with gender, biological maturity and body fat—The HELENA Study

Abstract: Background/Objectives: To provide a detailed lipid profile of a European adolescent population considering age, gender, biological maturity, body mass index (BMI), fat mass (FM) and percentage body fat (BF). Subjects/Methods: Within Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA), a cross-sectional study was conducted to determine fasting serum concentrations of lipids, lipoproteins and apolipoproteins in 1076 adolescents aged 12.5-17.49 years from ten European centres. Results: All serum lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
5
16
2
Order By: Relevance
“…Vitamin E is transported in circulation by plasma lipoproteins mainly LDL and HDL [ 23 , 24 ]. Mean cholesterol values reported in this study were closed to those reported in European children and adolescents in the HELENA and IDEFICS studies [ 25 , 26 ] and slightly lower than those reported among French children [ 27 – 29 ]. Since α-tocopherol is known to increase with the degree of hyperlipidemia and is dependent on lipid metabolism for delivery to tissues, adjustment for total cholesterol or lipids is also important to assess vitamin E status in some special conditions such as cholestasis or cystic fibrosis [ 24 , 30 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Vitamin E is transported in circulation by plasma lipoproteins mainly LDL and HDL [ 23 , 24 ]. Mean cholesterol values reported in this study were closed to those reported in European children and adolescents in the HELENA and IDEFICS studies [ 25 , 26 ] and slightly lower than those reported among French children [ 27 – 29 ]. Since α-tocopherol is known to increase with the degree of hyperlipidemia and is dependent on lipid metabolism for delivery to tissues, adjustment for total cholesterol or lipids is also important to assess vitamin E status in some special conditions such as cholestasis or cystic fibrosis [ 24 , 30 ].…”
Section: Discussioncontrasting
confidence: 83%
“…It has been reported that obesity is associated with an increased cholesterol synthesis rate, equal to about 20 mg d −1 for each kilogram of body fat . BMI was shown to be positively correlated with TG and LDL‐C, and negatively with HDL‐C ; and overweight/obesity is positively associated with the prevalence of dyslipidaemia in adolescents . Our review finds that 70% of the interventions had a similar effect on adiposity measures and blood lipids; interventions having a significant desirable effect on adiposity measures led to a significantly greater improvement in LDL‐C, HDL‐C and TG.…”
Section: Discussionmentioning
confidence: 54%
“…It is worthwhile comparing the data from this cohort of European children with those from another European cohort of adolescents (HELENA 42 ) studied in 2006-hence comparing two European birth cohorts with a time interval of on average around 6 years.…”
Section: Discussionmentioning
confidence: 99%